Life on the edge: the plankton and chemistry of Beaver Lake, an ultra-oligotrophic epishelf lake, Antarctica - Laybourn-Parry, J; Quayle, W; Henshaw, T; Ruddell, A; Marchant, HJ (2001)
1. Beaver Lake, a large epishelf lake in eastern Antarctica was sampled on two occasions during the austral summer of 2000. Two sites, one 1 km offshore and another 6 km offshore were sampled at intervals to depths of 40 and 110 m, respectively. 2. The lake is an end member of ultra-oligotrophic lake systems with a very low carbon pool. Dissolved organic carbon concentrations ranged between 95 and 652 Î¼g L -1. Nutrient levels were generally low with soluble reactive phosphorus ranging from undetectable to 8.4 Î¼g L -1, ammonium ranged between 1.8 and 5.0 Î¼g L -1, nitrate from undetectable to 161 Î¼g L -1 and nitrite 1.1-5.3 Î¼g L -1. 3. Chlorophyll a concentrations (0.39-4.38 Î¼g L -1) showed an unusual distribution with the highest levels close to the lake bottom at the offshore site (110 m) where the phototrophic nanoflagellates (PNAN) displayed strong autofluorescence. 4. Bacterial concentrations were low, with a maximum of 7.60 Ã— 10 7 L -1, as were the concentrations of heterotrophic nanoflagellates that exploit them. 5. Primary production ranged between 19.7 and 25.49 Î¼g C L -1 day -1 and bacterial production from 0.32 to 1.15 Î¼g C L -1 day -1. 6. In common with other continental Antarctic lakes, the system was dominated by a microbial plankton. However, a dwarf variety of the calanoid copepod, Boeckella poppei, occurred below 25 m at concentrations of 3-5 L -1. 7. The data suggest that primary production and bacterial production were not limited by nutrient availability, but by other factors, e.g. in the case of bacterial production by organic carbon concentrations and primary production by low temperatures.